Pembinaan Aspek Internal dan Eksternal untuk Mendorong Reformasi dan Perbaikan Kualitas Pelayanan Publik - Sulistywati Sulitywati (Jurnal Good Governance, 2017)
Along with the development of the dynamics of the society, globalization of the world and the demands of national bureaucratic reform, the public demands Civil Servants to carry out public services that are accountable, responsive, service-oriented professional, transparent, easy, cheap, fast and not convoluted. To build public trust to Civil Servants focused on internal and external structuring of Civil Serants in order to improve the quality of public services. The research method used in this research is the method of library (library research). The purpose of good governance is the realization of partnership of civil servants and community (sommunity) to achieve trust and welfare of the community. To enable the establishment of a good governance partnership as outlined above, the objective is to build a credible civil servant by the community and build a community ready to partner with civil servants. Keywords: bureaucratic reform, civil servant, good governance, service quality, trust